Exploring the molecular interactions of 4,4′-dichlorodiphenyldichloroethylene, imidacloprid, lambda-cyhalothrin, and malathion with antioxidant enzymes and their relevance to oxidative stress - Prem Rajak; Abhratanu Ganguly; Sayantani Nanda (Green Analytical Chemistry)
Oxidative stress is a detrimental condition that occurs when there is an imbalance between sub-cellular antioxidants and free radicals. Endogenous antioxidants actively scavenge free radicals and prevent oxidative stress. Pesticides can affect antioxidant activities. However, molecular interactions between the pesticides and endogenous antioxidants are not clear. Hence, objective of the present study is to dissect the intermolecular interactions between the widely-used pesticides (4,4′-dichlorodiphenyldichloroethylene, 4,4′-DDE; imidacloprid, IMD; lambda-cyhalothrin, CYH; malathion, MAL) and major antioxidant enzymes (Glutathione peroxidase-4, Glutathione S-Transferase, Catalase, Glutathione reductase, Superoxide dismutase-1) that might be responsible for altered enzyme activities and induction of oxidative stress. The binding affinity analysis using AutoDock vina and Discovery Studio Visualizer was conducted to unveil the potential intermolecular interactions between the pesticides and antioxidants. In the results, 4,4′-DDE, IMD, CYH, and MAL interacted with the antioxidants through stable hydrogen bonds, carbon-hydrogen bonds, van der Waals, and other hydrophobic interactions. Additionally, considerable binding affinities between the pesticides and enzymes were noted. ADME analyses have also revealed that the majority of pesticides can cross GI, exhibit low to high water solubility, and follow Lipinski's rule. Hence, results of the present study suggest that pesticides can potentially interact with antioxidants to modulate their catalytic activity and induce oxidative stress.